Sternocleidomastoid flap repair for pharyngo-cutaneous fistula complicating parapharyngeal abscess: a case report / Yee Pui Mun ... [et al.] - Yee, Pui Mun; Sultan Abdul Kader, Mohamed Iliyas; Abdullah, Abdul Mokthi; Heng, Pek Ser; Tang, Ing Ping (Faculty of Medicine, 2022)
Pharyngo-cutaneous fistulas (PCF) are commonly seen in major hypopharyngeal and laryngeal post-operative patients. Reports of PCF as a complication of deep neck abscess is scarce. The majority of post total laryngectomy PCF closure are achieved via conservative management, only large fistulas requires surgical closure. However, there is little evidence on closure of fistulas from abscess origin shall there be a failure of conservative treatment. We present a case of a female patient with multiple comorbid who had left parapharyngeal abscess complicated with PCF who have successfully treated sternocleidomastoid pedicle flap repair.